Clinical and Epidemiologic Features of Pediatric Strongyloidiasis in Spain - Jose Antonio Soler-Simón; Álvaro Díaz Conradi; María del Mar Santos Sebastián; María Espiau; Antoni Soriano-Arandes; Alicia Hernanz Lobo; Sara Guillén; Cristina Epalza; Cinta Moraleda; Manuel Oltra Benavent; Anna Vidal-Moreso; Filip Camil Olteanu Olteanu; et al. (Pediatric Infectious Disease Journal, 2026)
Background: Data about pediatric strongyloidiasis are scarce in our setting. Methods: We conducted a retrospective multicenter registry of cases of pediatric strongyloidiasis in Spain. Results: Among 138 cases, 76% were travelers/migrants. Overall, 32% were symptomatic, and 35% had eosinophilia (higher in symptomatic patients, P < 0.05). Confirmed diagnosis occurred in 10% (stool polymerase chain reaction), while 90% were probable (serology). Ivermectin was the first therapy (98%). Adequate follow-up after treatment was achieved in only 36%. Conclusions: One-fourth of cases were authochthonous, so screening should not be limited to migrant children. Mild eosinophilia could help to detect asymptomatic cases.